The lady was a gambler : true stories of notorious women of the old West - Enss, Chris, 1961- (TwoDot, 2008)
Amidst the mining camps, cattle ranches, desolate landscapes, and gold mining towns of the Wild West were a succession of women who survived dangerous gambling games against ruthless men whose pride was staked on always having the upper hand."The Lady Was a Gambler" presents a collection of action-filled portraits of fifteen infamous women gamblers from the Old West. Among those profiled are "Poker" Alice Ivers, the finest player bar none from Deadwood to Tombstone; Eleanora Dumont, the West's hottest twenty-one dealer; and Lottie Deno, the beautiful faro dealer who gambled all the way from Texas to Alaska.